Effect of steaming-up-period on subsequent production in primiparous crossbred dairy cows - DAS, K S; TOMER, O S; DAS, N; BISHT, G S; SANYAL, M K (The Indian Journal of Animal Sciences, 2014)
An experiment was carried out on 36 crossbred (Jersey, Holstein-Friesian and Hariana) pregnant heifers maintained under loose housing and group management systems for 90, 60 and 30 days prepartum till 150 days of ensuing lactation, The animals were selected on the basis of similarity in agc and body weight. Over and above the scheduled amount of concentrate (@ 215 kg/animal/day), all the 36 experimental animals in 3 groups were ollered additional 60 kg concentrate at different duration viz, @0,5 kg/day during seventh and eight month of pregnancy followed by @ 1 kg/day during ninth month of pregnancy in first group; @ 1 kg/day for last 60 days of pregnancy in second group and @ 2 kg/day in last 30 days of pregnancy in third group, After calving, the animals were fed according to the milk yield i.e, 2 kg concentrate for maintenance plus 1 kg for every 2,5 kg milk production. Ad lib. green fodder and fresh water were provided throughout 24 hr; It was observed that although there were no significant differences between 3 fceding groups, 90 days feeding group animals performed better than other 2 groups in terms of 150 days subsequent milk production, time taken to attain peak yield, peak yield and 150 days yield of milk fat, SNF, protein and casein. Thus, 90 days feeding period may be recommended for better production, performance of animals in the subsequent lactation.